Crocus sativus L.: A comprehensive review - Srivastava, R.; Ahmed, H.; Dixit, R. K.; D, Dharamveer; Saraf, S. A. (Pharmacognosy Reviews)
Crocus sativus L. belonging to the family Iridaceae (syn - kesar) comprises the dried red stigma and is widely cultivated in Iran and other countries such as India and Greece. Saffron contains more than 150 volatile and aroma-yielding compounds mainly terpenes, terpene alcohol, and their esters. The bitter taste and an iodoform or hay-like fragrance are caused by chemicals picrocrocin and safranal. C. sativus possesses a number of medicinally important activities such as antihypertensive, anticonvulsant, antitussive, antigenototoxic and cytotoxic effects, anxiolytic aphrodisiac, antioxidant, antidepressant, antinociceptive , anti-inflammatory, and relaxant activity. It also improves memory and learning skills, and increases blood flow in retina and choroid. The present review explores the historical background, chemical constituents, pharmacological actions, uses, substitutes and adulterants, and toxicity. It also deals with its evaluation, formulations, and chemical tests in detail.
Keywords: Anticonvulsant; antinociceptive; aphrodisiac; crocin; Crocus sativus; safranal